State Ownership, Political Institutions, and Stock Price Informativeness: Evidence from Privatization - Ben-Nasr, Hamdi; Cosset, Jean-Claude (Journal of Corporate Finance, 2014)
In this paper, we examine the relation between government ownership and stock price informativeness around the world. Using a sample of privatized firms from 41 countries between 1980 and 2012, we find strong and robust evidence that state ownership is associated with lower firm-level stock price variation, i.e., stock price informativeness. Furthermore, we find that the relation between state ownership and stock price informativeness depends on political institutions. In particular, the adverse effects of state ownership on stock price informativeness are more pronounced in countries with lower political rights (i.e., lower political constraints on the government).